Psychomotor coordination and intelligence in childhood and health in adulthood--testing the system integrity hypothesis. - Gale, C; Batty, G; Cooper, C; Deary, I (2009)
OBJECTIVES: To examine associations between intelligence and psychomotor coordination in childhood and risk of psychological distress, poorer self-rated health, and obesity in adulthood. To investigate whether psychomotor coordination as a potential marker of the construct "system integrity" explains associations between intelligence and these outcomes. METHODS: Participants were members of two British national birth cohorts: the 1958 National Child Development Survey (n = 6147) and the 1970 British Cohort Study (n = 6475). They took tests of psychomotor coordination and intelligence at age 10 to 11 years and reported on their health when in their early 30s. RESULTS: For a standard deviation increase in psychomotor coordination score, sex-adjusted odds ratios (95% CI) for the 1958 and 1970 cohorts, respectively, were 0.79 (0.72-0.87) and 0.83 (0.77-0.89) for psychological distress, 0.79 (0.73-0.85) and 0.85 (0.78-0.91) for fair/poor self-rated health, and 0.81 (0.75-0.88) and 0.85 (0.78-0.92) for obesity. These associations were independent of childhood intelligence and most remained significant after adjustment for other covariates. Higher intelligence quotient was associated with a reduced risk of psychological distress, fair/poor self-rated health, and obesity in adulthood. These associations were not explained by potential confounding factors or by psychomotor coordination in childhood. CONCLUSION: Having better psychomotor coordination in childhood seems protective for some aspects of health in adulthood. Examination of the role played by other markers of the efficiency of the central nervous system may help reveal the extent to which system integrity underlies the link between intelligence and health.